A visão do professor sobre o aluno surdo no Ensino Fundamental - Cabral, Lilian Della Torre Sousa (2016)
This research aimed to investigate the learning potential of deaf students in Elementary Education from the perspective of their teachers. The research is qualitative. I tried to describe in detail the views and ideas of the teachers about their student with deafness, learning and inclusion in the common room. For this study, we selected two teachers from state schools in the city of São Paulo. The criteria for selection of the teachers were: more than five years of professional experience and work with deaf students in the common room. The two teachers in the study work in the same state school located in Guaianases neighborhood on the outskirts of São Paulo. Data were collected during the school year 2016, by applying a semistructured interview that left the following questions: How do you see your student with deafness in the classroom? How do you see the learning and the potential of their deaf student? How do you see his relationship with the other students? From these questions were appearing in the speech of teachers aspects related to the identity of the deaf student, the reception of teachers to students with disabilities, the role of LIBRAS interpreter and the importance of teaching LIBRAS. In speaking of the teachers it was evident that students with hearing loss has the same potential to learn from their peers of the same age, provided that an appropriate pedagogy is applied. In view of this, it would be necessary to seek new avenues for teaching activities that are more targeted to the student's learning possibilities with disabilities and not just focusing on the difficulties of learning and inclusion. It was also possible to see in the statements of the teachers the benefits of inclusion of a deaf student to the other room the students through the learning LIBRAS and living with differences